Pelatihan Pengembangan Desa Wisata Melalui Digitalisasi Dan Inovasi Produk Wisata Di Desa Sibetan, Kabupaten Karangasem, Bali - Putu Surya Laksana Rahjasa; Putu Ayu Aryasih; Gede Ngurah Primanda S Rahadiarta (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
Sibetan Village in Karangasem Regency, Bali, has great tourism potential but has not been optimally utilized due to a lack of digitalization and tourism product innovation. This article is the result of community service activities aimed at enhancing the digitalization skills and tourism product innovation of the Sibetan Village community. The training included the use of digital technology in the promotion and management of tourist destinations, as well as the development of unique and sustainable tourism products. The method of implementation consisted of lectures, discussions, and practical sessions. The results showed an improvement in participants' understanding and skills in using digital media for promotion and managing tourism products. Participants also began developing new tourism packages, such as the Bali salak agro-tourism, with more innovative and sustainable approaches. Participant satisfaction with the program was very high, with an average score above 3.8 out of 4 on various evaluation indicators. In conclusion, this program successfully empowered the community to utilize digital technology and tourism product innovation to increase tourism appeal and the economic welfare of the community. Follow-up activities involving intensive mentoring are proposed to optimize the results of the training.